The Monogram Murders : The New Hercule Poirot Mystery - Christie, Agatha (London HarperCollins Publishers, 2014)
The new Hercule Poirot novel - another brilliant murder mystery that can only be solved by the eponymous Belgian detective and his 'little grey cells'.
The New Hercule Poirot Mystery.
Keywords: Poirot, Hercule (Fictitious character) -- Private investigators -- Belgium -- England--London